Sources of Support for Studies That Inform Recommendations of the Community Preventive Services Task Force. (November 2020) - Neilson, Elizabeth; Villani, Jennifer; Mercer, Shawna L.; Tilley, David L.; Vincent, Isaah; Alston, Anita; Klabunde, Carrie N.
Objectives: The Community Preventive Services Task Force (CPSTF) makes evidence-based recommendations about preventive services, programs, and policies in community settings to improve public health. CPSTF recommendations are based on systematic evidence reviews. This study examined the sponsors (ie, sources of financial, material, or intellectual support) for publications included in systematic reviews used by the CPSTF to make recommendations during a 9-year period. Methods: We examined systematic evidence reviews (effectiveness reviews and economic reviews) for CPSTF findings issued from January 1, 2010, through December 31, 2018. We assessed study publications used in these reviews for sources of support; we classified sources as government, nonprofit, industry, or no identified support. We also identified country of origin for each sponsor and the most frequently mentioned sponsors. Results: The CPSTF issued findings based on 144 systematic reviews (106 effectiveness reviews and 38 economic reviews). These reviews included 3846 publications: 3363 publications in effectiveness reviews and 483 publications in economic reviews. Government agencies supported 57.1% (n = 1919) of publications in effectiveness reviews and 59.2% (n = 286) in economic reviews. More than 1500 study sponsors from 36 countries provided support. The National Institutes of Health was the leading sponsor for effectiveness reviews (21.3%; 718 of 3363) and economic reviews (16.2%; 78 of 480), followed by the Centers for Disease Control and Prevention (7.0%; 234 of 3363 effectiveness reviews and 14.8%; 71 of 480 economic reviews). Conclusions: The evidence base used by the CPSTF was supported by an array of sponsors, with government agencies providing the most support. Study findings highlight the need for sponsorship transparency and the role of government as a leading supporter of studies that underpin CPSTF recommendations for improving public health.